2015
DOI: 10.1021/acs.jpcc.5b02286
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystal Formation in Silicon Oxy-Nitride Films for Photovoltaic Applications: Optical and Electrical Properties

Abstract: Thin films of nanocrystalline SiO x N y are studied in view of their application in silicon heterojunction (SHJ) solar cells. In particular, the formation of the nanocrystals and their effects on the electrical and optical properties of the films are investigated. The role of the oxygen content on the properties of the layers is clarified as well. The obtained layers show very high conductivity (44 S/cm), low activation energy (1.85 meV) and high Tauc gap (2.5 eV), promising features for their application in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…5(b) that the sample becomes more transparent after annealing. It has been reported that optical band gap is enlarged after annealing in B-doped nc-SiO x N y films, 13 which was explained as the contribution both from the quantum confinement effects and the increased amount of SiO x composition due to formation of Si nano-crystals. In our previous work, we also found that the existence of grain boundary after annealing can influence the optical band gap obviously.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5(b) that the sample becomes more transparent after annealing. It has been reported that optical band gap is enlarged after annealing in B-doped nc-SiO x N y films, 13 which was explained as the contribution both from the quantum confinement effects and the increased amount of SiO x composition due to formation of Si nano-crystals. In our previous work, we also found that the existence of grain boundary after annealing can influence the optical band gap obviously.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 7, when doping ratio R is lower than 0.6, the relationship between dark conductivity σ and the temperature T can be well described as the formula, which usually used to describe the transport process in micro-crystalline and nano-crystalline Si-based materials: 13,28 …”
Section: -6mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to coexistence of different phases and compositions upon annealing, the structure and the formation of SiO x N y together with the role of crystalline fraction and oxygen content in changing optical and electrical properties are still unclear. The dependence of conductivity and optical band gap from oxygen content has been investigated only recently in amorphous and annealed SiO x N y [2,16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%